2023
DOI: 10.1007/s10552-023-01677-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of higher-grade dysplasia in persistently high-risk human papillomavirus positive, cytology negative women after introduction of the new cervical cancer screening in Germany

Abstract: Purpose According to the recently implemented organized cervical cancer screening program in Germany, women older than 35 years with negative cytology but persistent high-risk human papilloma virus (hrHPV) infection > 12 months should be referred to colposcopy for further evaluation. This study aimed to present and dissect colposcopic and histopathological findings with particular focus on associated hrHPV genotypes. Methods This study is a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
1
3
0
2
Order By: Relevance
“…Thus, we demonstrated that colposcopic major change findings were assigned three times more frequently in patients with group II-a (NILM) than in patients with group I (NILM). The rate of major changes in patients with group I (NILM) correlates with the data from Berger et al (2023) 2020 . However, in this small case study, no subgroup analysis was performed between groups I (NILM) and II-a (NILM), but all patients with normal cytological findings were evaluated together.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Thus, we demonstrated that colposcopic major change findings were assigned three times more frequently in patients with group II-a (NILM) than in patients with group I (NILM). The rate of major changes in patients with group I (NILM) correlates with the data from Berger et al (2023) 2020 . However, in this small case study, no subgroup analysis was performed between groups I (NILM) and II-a (NILM), but all patients with normal cytological findings were evaluated together.…”
Section: Discussionsupporting
confidence: 86%
“…In the group of participants presenting with cytology group II-p (535), colposcopically minor changes were most frequent (54.8 %, 291), followed by physiological changes with 26.6 % (141). Major changes were detected in 13.6 % (72) and nonspecific abnormal findings in 3.8 % (20). Other findings were found in 1.3 % of cases (7).…”
Section: Group Ii-p (Asc-us)mentioning
confidence: 95%
See 2 more Smart Citations
“…However, a recent retrospective analysis showed that in 60% of cases with a positive hrHPV result, but negative Pap, had positive colposcopic findings (either minor or major). 21 This provides strong evidence that most patients would benefit from cotesting with a Pap smear and HPV Conversely, we identified hrHPV positive cases that were not associated with any detectable abnormalities, but no conclusions can be made with regard to the infection due to the absence of follow-up visits. The positive expression for p16/Ki-67 has proven to be extremely important in triaging patients diagnosed with ASC-US/LSIL, or non-HPV16/18 hrHPV types.…”
Section: Overexpression Of Cell Cycle Markers P16/ki-67 In Hrhpv Pati...mentioning
confidence: 80%